Interobserver reliability of histopathological features for distinguishing between cutaneous polyarteritis nodosa and superficial thrombophlebitis - Parnhathai Hutachuda (2019)
© 2018 John Wiley & Sons Ltd Aims: Interobserver reliability of histopathological features in differentiation between cutaneous polyarteritis nodosa (cPAN) and superficial thrombophlebitis (ST) by assessment of inter-rater agreement of five histological features was investigated. Methods and results: All sections of cPAN and ST were evaluated independently by three experienced pathologists and one resident of pathology. The histopathological features studied included elastic fibre distribution in the vascular wall, a smooth muscle arrangement pattern, an internal elastic lamina pattern, fibrinoid necrosis and luminal thrombosis. Agreement analysis was performed using the kappa coefficient. Sensitivity, specificity, positive predictive value (PPV), positive likelihood ratio (PLR) and 95% confidence interval (95% CI) of the useful histopathological features were analysed. Of all 62 biopsies, 28 were cPAN and 34 were ST. Reproducibility between four observers was in substantial agreement (κ = 0.73). Elastic fibre distribution in the vascular wall (κ = 0.68), fibrinoid necrosis (κ = 0.63), an internal elastic lamina pattern (κ = 0.51) and a smooth muscle arrangement pattern (κ = 0.46) showed high specificity and PPV for differentiating between cPAN and ST. The smooth muscle arrangement pattern, internal elastic lamina pattern and elastic fibre distribution in the vascular wall may be obscured when extensive inflammation and necrosis occurs. Conclusions: These aforementioned histopathological features are useful in differentiation between cPAN and ST. The Verhoeff–van Gieson (VVG) elastic stain is an important histochemical study for differentiating between cPAN and ST, particularly in cases with extensive inflammation and necrosis.